Untargeted Metabolomics Yields Insights Into the Lipidome of Botrylloides niger Herdman, 1886, An Ascidian Invading the Mediterranean Sea - Della Sala, Gerardo; Coppola, Daniela; Virgili, Riccardo; Vitale, Giovanni Andrea; Tanduo, Valentina; Teta, Roberta; Crocetta, Fabio; de Pascale, Donatella (Frontiers in Marine Science, 2022)
Human-mediated dispersal of alien species in new biogeographic realms is one of the major drivers of biodiversity change in marine ecosystems. Among others, ascidians are invasive species spreading worldwide, thus causing ecological and economic harms in the recipient environments. An integrated taxonomic approach on selected samples allowed the identification of Botrylloides niger Herdman 1886 as a non-indigenous ascidian forming large aggregates and outcompeting native species in the Fusaro Lake (central-western Mediterranean Sea). This led to the opportunity to investigate in deep its metabolome for the first time. Untargeted mass spectrometry-based metabolomics unveiled B. niger to be a source of nutraceuticals and bioactive natural products, such as lysophospholipids, sulfonolipids, polyunsaturated fatty acids, sphingolipids, monoacylglycerols, and alkaloids. Even if causing ecosystem alterations, our results suggest that B. niger could be exploited for nutritional and/or pharmaceutical purposes, thereby turning a treat in a resource.